A chlorinated dihydrobenzofuran from Flourensia riparia - Uriburu, M.L. (2005)
A new chlorinated compound, 5-acetyl-2,3-dihydro-2- (2-[1-chloro-2-hydroxypropyl])-benzofuran has been isolated from the chloroformic extract of the aerial parts of Flourensia riparia Griseb., along with the previously known benzofuran 2,3-dihydro-11,12-dihydroxyeuparin. Structural characterization was carried out by spectroscopic methods.